Biography of the Philosopher by Abū al-Khayr al-Ḥasan ibn Suwār (Ibn al-Khammar) - Mesbah, Mohamed Magdy Elsayed (Nama Journal of Islamic Sciences and Humanities, 2023)
This study aimed to find out the philosophers ’opinion about the characteristics of the philosopher, and Ibn al-Khammar was taken as a model for it. It also aimed to reveal the extent to which this philosopher was influenced by his predecessors in this matter, whether from the philosophers of Greece or Islam. This study also focused on uncovering and discussing the moral views of the philosopher Ibn al- Khammar, in terms of: the conditions befitting the philosopher, the issue of moral imperative and what falls under it as the sources of this obligation and its many aspects. This study relied mainly on Ibn al-Khammar’s essay called “An Essay on the Character of a Philosopher,” which was investigated within this study. This study reached several conclusions, most notably: Reason is one of the most basic sources of moral imperative according to Ibn al- Khammar, according to which the morality of an action is determined. Ibn Al-Khammar did not deviate from the traditions of the Baghdad Rational School and its extensions in the connection between logic and medicine. Ibn al- Khammar remained faithful to the philosophical school (Greek and Islamic) in its treatment of the philosophical biography or the characteristics of the philosopher. So he quoted them, went back to them, and made their statements an indication and evidence of the validity of his statements.